Determining optimal groundwater table depth for maximizing cotton production in the Sardarya Province of Uzbekistan - Qureshi, Asad Sarwar; Eshmuratov, Davron; Bezborodov, G.A. (Wiley, 2011)
Poor on-farm irrigation practices and rising groundwater table depths are the major reasons for low cotton yields in the Sardarya province of Uzbekistan. To ensure sustainability of cotton production in the area, precise calculations of irrigation requirements are needed to optimize crop yields and to keep groundwater table depth below the root zone to avoid soil salinization. To determine optimal groundwater table depth and irrigation amounts for the Sardarya province of Uzbekistan, the Soil-Water-Atmosphere-Plant (SWAP) model was used. SWAP was calibrated and validated using measured data from an experimental cotton field during the agricultural year of 2006 and 2007. The calibrated SWAP model was then used to simulate optimal groundwater table depth and irrigation amounts. The simulation results show that for the existing conditions in the study area, a groundwater table depth of approximately 200 cm together with an irrigation application of 2500m3 ha1 will be the most appropriate combination for optimal cotton yields ( 3.0 t ha1). However, to achieve maximum potential yields of cotton (5-6 t ha1), leaching of excessive salts from the root zone through freshwater application would be imperative. This would require rehabilitation of the existing drainage network in the area.